Updating the determinants of health model in the Information Age. (12th September 2018) - Rice, Louis; Sara, Rachel
Abstract: In 1991, Dahlgren and Whitehead produced a highly influential model of the determinants of health that has since been used by numerous national and international public health organizations globally. The purpose of the model is to enable interventions that improve health to be addressed at four key policy levels. It is not a model of health or disease; instead the model is structured around health policy decision-making. However the model needs an update, since it was devised there has been a digital revolution that has transformed every aspect of: human life, our cities, society and the fundamental principles upon which the global economy operates. The article examines the impact of Information and Communication Technologies (ICT) on the determinants of health. ICT has given rise to a new Information Age that is implicated in many of the major global health issues today. Addressing contemporary health issues requires intervention at the level of ICT, particularly as health communication online is central to the delivery and dissemination of public health policies.